2018
DOI: 10.1007/s00464-018-6437-0
|View full text |Cite
|
Sign up to set email alerts
|

High cardiovascular risk patients benefit more from bariatric surgery than low cardiovascular risk patients

Abstract: Study results suggest ASCVD and FRS are equally reduced after bariatric surgery, especially after LSG and LRYGB. Moreover, preoperative FRS and ASCVD risk score showed an inversely proportional relationship with %EBMIL loss at 12 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…At 6 months follow-up, there was a significant decrease in the estimated risk of fatal or nonfatal coronary events in 10 years according to the Framingham risk score (P < 0.0001) and estimated vascular age (P < 0.0001). In a recent study conducted by Blanco et al [28] involving 360 patients with bariatric surgery, LSG was the most prevalent surgery (63%), followed by RYGB (20.6%), and reported significant reduction of both atherosclerotic cardiovascular disease and Framingham risk scores at 12 months. In another study, Wei et al [29] recently investigated the benefit of CVD risk reduction after metabolic surgery in 392 obese patients with type 2 DM who had undergone LSG (87) or RYGB (305).…”
Section: Discussionmentioning
confidence: 97%
“…At 6 months follow-up, there was a significant decrease in the estimated risk of fatal or nonfatal coronary events in 10 years according to the Framingham risk score (P < 0.0001) and estimated vascular age (P < 0.0001). In a recent study conducted by Blanco et al [28] involving 360 patients with bariatric surgery, LSG was the most prevalent surgery (63%), followed by RYGB (20.6%), and reported significant reduction of both atherosclerotic cardiovascular disease and Framingham risk scores at 12 months. In another study, Wei et al [29] recently investigated the benefit of CVD risk reduction after metabolic surgery in 392 obese patients with type 2 DM who had undergone LSG (87) or RYGB (305).…”
Section: Discussionmentioning
confidence: 97%
“…26 A retrospective observational study of 1330 people with no history of CVD undergoing bariatric surgery between 2010 and 2016 suggested that those with severe obesity and high risk of CVD benefit more from the procedure than those with obesity and low CV risk. 27 F I G U R E 1 Association of excess adiposity with major risk factors and chronic conditions. 3 Common chronic diseases are shown in red boxes.…”
Section: Bariatric Surgerymentioning
confidence: 99%